Secreted TARSH Regulates Olfactory Mitral Cell Dendritic Complexity - Cheng, Ting-Wen (2009)
Olfactory sensory neurons synapse with mitral cells to form stereotyped connections in the olfactory bulb. Mitral cell apical dendrites receive input from olfactory sensory neurons expressing the same odorant receptor. During development, this restricted dendritic targeting of mitral cells is achieved through eliminating elaborated dendritic trees to a single apical dendrite. Through a genome-wide microarray screen, we identified TARSH as a transiently expressed molecule in mitral cells during the dendritic refinement period. TARSH expression is restricted to pyramidal neurons along the main olfactory pathway, including the anterior olfactory nucleus and piriform cortex. The dynamic TARSH expression is not altered when odor-evoked activity is blocked by naris closure or in AC3 knock-out mice. We also demonstrate that TARSH is a secreted protein. In dissociated olfactory bulb cultures, secreted TARSH promotes the reduction of mitral cell dendritic complexity and restricts dendritic branching and outgrowth of interneurons. Dendritic morphological changes were also observed in mitral cells overexpressing TARSH themselves. We propose that TARSH is part of the genetic program that regulates mitral cell dendritic refinement.